The Anglo-Scottish Ballad and its Imaginary Contexts - Atkinson, David (Open Book Publishers, 2014)
This is the first book to combine contemporary debates in ballad studies with the insights of modern textual scholarship. Just like canonical literature and music, the ballad should not be seen as a uniquely authentic item inextricably tied to a documented source, but rather as an unstable structure subject to the vagaries of production, reception, and editing. Among the matters addressed are topics central to the subject, including ballad origins, oral and printed transmission, sound and writing, agency and editing, and textual and melodic indeterminacy and instability. While drawing on the time-honoured materials of ballad studies, the book offers a theoretical framework for the discipline to complement the largely ethnographic approach that has dominated in recent decades. Primarily directed at the community of ballad and folk song scholars, the book will be of interest to researchers in several adjacent fields, including folklore, oral literature, ethnomusicology, and textual scholarship.